Vision 2020 through science and technology : proceedings of the 6th Science and Technology Congress and Seminar, Kuala Lumpur, August 7-13, 1992 - Science and Technology Congress and Seminar (6th : 1992 : Kuala Lumpur) (Kuala Lumpur : [Conference Secretariat], 1992)
39